Evaluation of Novel Approaches to Software Engineering : 14th International Conference, ENASE 2019, Heraklion, Crete, Greece, May 4–5, 2019, Revised Selected Papers /: 14th International Conference, ENASE 2019, Heraklion, Crete, Greece, May 4–5, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available